Capacity Building for Sheep Farming Entrepreneurship: Focusing on Potential and Management Aspects at Nurul Hikmah Pondok Pesantren, Sumedang - Alhuur, Ken Ratu gharizah; Nurmeidiansyah, An An (Farmers: Journal of Community Services, 2024)
Alleviating the problem of unemployment and poverty is being intensively carried out by the Sumedang Regency Manpower Office, one of the ways this is being done is by encouraging people to run businesses in the livestock sector. One of the places that received assistance in the form of 12 Garut sheep and their supporting needs were the students and administrators of the Nurul Hikmah Islamic Boarding School (Ponpes), Wado, Sumedang Regency. The hope is that this Islamic boarding school can provide provision for sheep farming business to its students, so that when they graduate from the Islamic boarding school, they can run a sheep breeding and fattening business which can be a good source of income for them. Collaboration between the Sumedang Regency Manpower Service and the Faculty of Animal Husbandry, Padjadjaran University in the form of mentoring activities is very important to equip aid recipients in running their businesses in the future, because the majority of livestock aid recipients do not have any background in animal husbandry at all. The first stage of the mentoring method is carried out by means of lectures and discussions, to explore the knowledge of the participants. The result of this activity was that 90.5% of the participants who were recipients of sheep livestock assistance had no knowledge or background in farming. This mentoring activity is very necessary to ensure the success of the livestock business assistance program in an effort to alleviate the problem of unemployment and poverty in Sumedang Regency.